Beta-adrenergic reactivity of erythrocytes and the progression of heart failure in patients after myocardial infarction - A. A. Garganeeva; V. A. Aleksandrenko; E. A. Kuzheleva; T. Yu. Rebrova (Российский кардиологический журнал)
Aim. To identify the associations between beta-adrenergic reactivity of erythrocytes and the progression of heart failure (HF) in patients after myocardial infarction (MI).Material and methods. The study included 50 patients with HF and history of MI 6 months ago. To determine the level of sympathoadrenal system activity, we analyzed beta-adrenergic reactivity by changing the osmotic resistance of erythrocytes by use of adrenoceptor blocking agent.Results. The frequency of HF progression after index MI was 26% (n=13). All patients were divided into 2 groups depending on the presence/absence of HF progression in the postinfarction period. When determining beta-adrenergic reactivity, it was found that patients with HF progression compared with patients without it had the higher level of beta-adrenergic reactivity of membrane (β-ARM) of erythrocytes: 58,8 (50,9; 78,0) CU and 46,8 (38,0; 66,3) CU, p=0,025). A ROC analysis made it possible to establish the β-ARM level ≥49,53 CU a cut-off point, which can be considered as a marker of HF progression in patients after MI (sensitivity 92,3%, specificity 62,2%). This level of β-ARM is associated with a more than five-fold increase of HF progression risk in patients after MI (OR 5,48; 95% CI 1,28-23,37; p=0,024).Conclusion. In patients with HF and MI history, there is a decrease in the adrenergic reactivity of erythrocyte cell membrane, which is reflected by an increase of β-ARM above normal range of 20 CU. At the same time, β-ARM in patients with HF progression compared with patients without it is significantly increased. Established cut-off point of β-ARM (≥49,53 CU) allows predicting the HF progression with high sensitivity and specificity.